Preservação de documentos arquivísticos digitais: um estudo dos fatores que podem comprometer o módulo eletrônico de protocolo do SIPAC da UFPB para os gestores - Guimarães Júnior, Mauro Porfírio Barbosa (2022)
Digital preservation standards have emerged based on a paradigm transition break for preservation, where archival custody is no longer exclusively in the archive, but shared in an environment that needs preservation requirements and policies, because there is a great risk of losing information in this environment. With the advance of technologies, the digital document can suffer from technological obsolescence, in hardware, software or support, and be easily changed, lost or destroyed if due care is not taken. In Brazil, a crime can be charged to anyone who defaces or destroys documents, regardless of support, as provided by Law 8159/91, of public and private archives. Therefore, documents need to be in line with the regulations, so that they can be considered authentic and reliable and run less risk of being lost forever. Thus, the objective of this work is to propose improvements to preserve the digital nato document of the electronic protocol module of the Integrated System of Assets and Contracts (SIPAC) of the Federal University of Paraíba (UFPB). The specific objectives of this study are to present the chain of custody of the born digital document of the electronic protocol module of the Integrated Assets and Contracts System (SIPAC) of the Federal University of Paraíba (UFPB); to identify the existing means of stable storage and security measures at UFPB to ensure the authenticity of digital archival documents in the long term and to propose improvements to preserve the born digital document of the electronic protocol module of the SIPAC of UFPB. As for the methodology, this is a research with a qualitative approach, whose purpose is to deepen the understanding of the phenomena. To analyze the data collected, the content analysis proposed by Bardin was used as a method. The survey and data production will be done in three stages: in the first, semi-structured interviews will be prepared to be applied in the sample of archivists and in the Information Technology team of UFPB; in the second, the parameters of authenticity for digital archival documents were specified from the literature; and in the third, it was investigated if the requirements necessary to consider the digital archival document authentic, from the interviewees' answers, are in accordance with Conarq's Resolution 37. In all, eight people participated in the research, four of them from the Central Archive team and four from the Information and Technology Superintendence team, whose data were collected in person in their respective work environments.